An Analysis of Hedging Devices on Students’ Presentation of Seminar on Language Based on The Gender - Muziatun Muziatun; Fahria Malabar; Nur Windi Sangketa (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2021)
This study focus on the hedging devices types proposed by Namasaraev in relation with the participants’ confidence which consisted of female and male participant toward Seminar on Language presentation. The study expects to reveal the propensity of hedging in female and male speeches. This study applied qualitative descriptive method to describe the data in which using documentation by recording the participants’ speech. The result, it proved that both participants contributed fifth types of hedging devices. In female participant, those types are modal auxiliary verb, lexical verb, approximation, ‘if’ clause, and filler. As same as female participant, the male produced same types unless the type of ‘if’ clause and produced the adverb type. The findings displayed the female participants were frequently produced the filler type in which indicated the lack of confidence. Meanwhile, the male participants preferred to use modal auxiliary verb in which delivering the assertiveness and certainty. This study expected can be guidance for the readers who want to know more about hedging, also this can be source for further researcher who interested in the same fields.